Factors Influencing Teacher Educators' Research Engagement in the Reform Process of Teacher Education Institutions in Myanmar. (December 2021) - Kyaw, May Thu
This study addresses how similar teacher education institutions differ in terms of teacher educators' research engagement and what causes these differences. Underlying factors were explored by comparing teacher educators' research engagement at two Education Colleges in Myanmar that differed in terms of the educators' research activities. Applying the qualitative case study research design, data were drawn from a document analysis and semi-structured interviews with the college principals and teacher educators. Institutional expectation and encouragement for teacher educators' research engagement, their views on research, ways of their research engagement, and the motives and challenges in each case were scrutinized using a summative approach to qualitative content analysis. The findings demonstrate that personal, institutional, policy-related, and system-related factors influence teacher educators' research engagement. This suggests that, apart from the consideration of intrinsic and extrinsic motivation, teacher educators' autonomy in their research engagement should be secured and their policy awareness and buy-in assured.